Occurrence of Clostridium perfringens in layer flocks of selected districts in Bangladesh: molecular typing, antimicrobial susceptibility (Asian-Australasian Journal of Bioscience and Biotechnology, 2022)
Necrotic enteritis (NE) is one of the important enteric diseases in poultry caused by Clostridium perfringens which leads to considerable economic losses for poultry raisers. The present research was carried out to estimate prevalence, risk factors and to confirm molecular pattern, antimicrobial susceptibility status of Clostridium perfringens in layer flocks in Mymensingh and Gazipur districts of Bangladesh, where a total of 287 samples were collected that comprised of water (30), workers’ hand washing (30), and feed (30) as environmental pooled samples; cloacal swab (150) and post mortem sample (intestine) (47) as individual samples, and evaluated by basic (culture, biochemical test), and finally toxinotyping multiplex PCR assays. The flock-level data on potential risk factors were collected through semi-structured interviews with the farm owners and evaluated via univariable and multivariable logistic regression analyses where a p-value of